Rethinking the Cape Town Property Developer: Understanding the local developer's perspective of the City of Cape Town Municipality and comparing this perspective to local Transit-Orientated Development policy constructs of the developer - Abdullah, Mohammed Perwez (Department of Construction Economics and Management, 2020)
Purpose – This dissertation investigated the degree to which the City of Cape Town understands a ‘notional' Cape Town property developer within the Transit-Orientated Development (“TOD”) context. This dissertation is not meant to draw a distinction between a right or wrong model of a local property developer, but to investigate what a richer model would look like using alternative economic perspectives that capture the multiplicity of reality and possible TOD policy implications. Design – A literature review was undertaken to understand institutional and behavioural economic frameworks, how each framework relates to the property market, and how to use the frameworks to assist in defining a developer. Further research was conducted to consider the property development process from the perspective of the Complex Adaptive Systems (CAS) framework. The property developer as an actor within the property market was then deconstructed. Alternative approaches to local government involvement in the development industry and the developer's perspective on TOD was also explored. A qualitative, semi-structured localist interview was conducted with nine major developers operating in Cape Town. They were selected because they are likely to participate in catalytic TOD-type projects. The interview aimed to understand their world view and how their lived experience relates to the City of Cape Town municipality. Findings – There is a ‘definition gap' between how the City of Cape Town has defined a developer and the findings of this dissertation. Policy implies a developer has perfect decision-making qualities pursuing maximum profits, whereas this dissertation found that developers tend to be focussed on risk reduction and exhibit satisficing and loss-averse behaviour. There are also those who prefer to build and hold a portfolio of rental properties which are not defined in policy. This type of developer possesses a different outlook and investment behaviour than the one defined in the TOD Strategic Framework. The City of Cape Town does not appreciate its positioning within and its influence on local property market dynamics, as it relates to the ‘rules of the game'. Practical Implications – Without understanding these distinctions, developers may not necessarily, predictably and readily respond to any TOD incentives and levers as set out in the Framework, resulting in policy perpetuating the very spatial inequalities and status quo the City of Cape Town aims to redress.